INTEGRASI PENDIDIKAN KARAKTER TANGGUNG JAWAB PADA PEMBELAJARAN BIOLOGI MATERI METODE ILMIAH MELALUI PEMBELAJARAN BERBASIS PROYEK BERBANTUAN FORMO - Trisni Atmawati (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
The research problem is how to integrate the character of responsibility in formo-based project-based learning and how to improve the character of student responsibilities after formo-based project-based learning. This research is a research and development research, with a sample of students of class X SMAN 1 Purworejo Lesson year 2017/2018. The results of this study are formo-assisted project-based learning that can integrate the character of responsibility through the use of formo planning at the end of the project preparation phase, the implementation formo at the project implementation stage and final form in the test result stage; 2) there is an increase of student responsibility from the beginning of preparation project up to the finished project ie from 80% to 100%.